2019
DOI: 10.1186/s12885-019-6125-z
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic HIPEC with radical D2 gastrectomy improves survival and peritoneal recurrence rates for locally advanced gastric cancer: personal experience from a randomized case control study

Abstract: Background To investigate the implications of prophylactic intraoperative Hyperthermic Intraperitoneal Chemotherapy (HIPEC) with D2 radical gastrectomy for locally advanced Gastric Cancer (AGC) in a randomized case control study. Method Eighty consecutive patients with locally AGC were randomly separated into 2 groups: HIPEC group (Curative Resection + intraoperative HIPEC with cisplatin 50 mg/m2 at 42.0 ± 1.0 °C for 60 min) and Control group (Curative Resection only). Intraoperative and post-operative event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 34 publications
2
62
1
8
Order By: Relevance
“…Previous findings suggest that the use of cytoreductive surgery plus HIPEC increases the risks of postoperative anastomotic leakage, intestinal fistula development, and abdominal bleeding[ 16 ]. However, in this study, the incidence of complications did not differ significantly between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that the use of cytoreductive surgery plus HIPEC increases the risks of postoperative anastomotic leakage, intestinal fistula development, and abdominal bleeding[ 16 ]. However, in this study, the incidence of complications did not differ significantly between groups.…”
Section: Discussionmentioning
confidence: 99%
“…To improve these recurrence rates, since 1988 several local treatment modalities have been studied for better local control and improved survival, such as HIPEC and more recently the extensive intraoperative peritoneal lavage with physiological saline . Evidence from earlier and recent trials along with at least three metanalysis suggests a survival benefit of adding HIPEC to a curative surgical procedure. What our study meant to investigate was if the same impact would be found in patients who were already treated with neoadjuvant chemotherapy, as it is now part of the standard multimodality therapy for gastric cancer …”
Section: Discussionmentioning
confidence: 99%
“…16 To improve these recurrence rates, since 1988 several local treatment modalities have been studied for better local control and improved survival, such as HIPEC 17 and more recently the extensive intraoperative peritoneal lavage with physiological saline. 18 Evidence from earlier 3,19 and recent trials 20,21 along with at least three metanalysis 4,5,22 suggests a survival benefit of adding HIPEC to a curative surgical procedure.…”
Section: Group Comparisonmentioning
confidence: 99%
“…In a study by Cui et al, where 192 AGC patients were randomly divided into the following four groups (control, NAC, HIPEC and combined groups), the results suggested that NAC combined with HIPEC for the treatment of AGC is well tolerated and exhibits improved compliance and efficiency [32]. In another study from our team, with a pool of 80 patients with 40 patients undergoing prophylactic HIPEC while the control group had surgery alone, the results showed that the experimental arm had significant survival benefit with a decrease in peritoneal metastatic rate [33].…”
Section: Prophylactic Hyperthermic Intraperitoneal Chemotherapymentioning
confidence: 99%